Pengaruh Media Sosial Dan Peer Pressure Terhadap Perilaku Konsumtif Mahasiswa Unisma Dengan Literasi Keuangan Sebagai Variabel Intervening - Aryani, Nisa Fadlilah; Farida, Eka; Normaladewi, Andi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to examine the influence of social media and peer pressure on the consumptive behavior of students at Universitas Islam Malang (Unisma), as well as the role of financial literacy as a mediator in this relationship. The population of this study consists of active undergraduate students at Universitas Islam Malang, with a sample of 100 respondents determined using Slovin's formula with a margin of error of 10%. The sampling technique used is Proportionate Stratified Random Sampling. This research adopts a quantitative approach with an explanatory research design. The type of data used in this study is primary data, obtained through the distribution of questionnaires using Google Forms. The questionnaire contains statements and response options using a 5-point Likert scale. The PLS-SEM (Partial Least Squares Structural Equation Modeling) approach, which comprises outer model analysis, inner model analysis, and hypothesis testing, was used to analyze the data using SmartPLS version 4.1.0.9. The findings show that Unisma students' consumption patterns are directly impacted by social media, peer pressure, and financial literacy. Additionally, the impact of peer pressure and social media on consumer behavior is mediated by financial literacy. Keywords: Social Media, Peer Pressure, Consumptive Behavior, Financial Literacy